Bioactive constituents, in vitro radical scavenging and antibacterial activities of selected Apis mellifera honey from Kenya - Mokaya, Hosea O. (Int J Food Sci Technol, 2019)
There is limited information about the relative composition and health benefits of various honey consumed across Africa. This study aimed at estimating the bioactive constituents, in vitro radical scavenging and antibacterial activities of 16 kinds of honey obtained from different geographical locations in Kenya. Manuka 5 + honey was included for comparison. Some of the tested honey had biochemicals and bioactivities similar to or higher than Manuka 5 + honey. The honey exhibited DPPH radical scavenging ability, with several types of honey showing superior scavenging potential than Manuka 5 + honey, owing to their high phenol content. All types of honey inhibited the growth of E. coli and further showed a substantial amount of nonperoxide antimicrobial activity. The geographical origin of honey had an influence on its bioactive contents. Overall, these findings suggest that Kenyan honey has great therapeutic potential, and thus, its clinical application should not be overlooked.